2006
DOI: 10.1097/01.sla.0000246856.03918.9a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Complications After Pancreatic Surgery

Abstract: This study demonstrates the applicability and utility of a new classification in grading complications following pancreatic surgery. This novel approach may provide a standardized, objective, and reproducible assessment of pancreas surgery enabling meaningful comparison among centers and over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
213
3
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 694 publications
(232 citation statements)
references
References 33 publications
13
213
3
3
Order By: Relevance
“…Recent efforts have attempted to clarify this and apply a grading system of complications in pancreatic surgery [26,29]. The ISGPS found that several definitions for DGE, POPF and PPH already existed and the study group recently standardised these definitions [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts have attempted to clarify this and apply a grading system of complications in pancreatic surgery [26,29]. The ISGPS found that several definitions for DGE, POPF and PPH already existed and the study group recently standardised these definitions [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Oncology surgery of the gastrointestinal tract is known for its high complication rates [1,2,3,4]. It usually involves extensive and complex surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although this technique was associated with lower rates of postoperative fistula than PJ, this surgical technique is not easy to reproduce and might not always be possible for oncological reasons [56] . This complexity may explain why gastric partitioning with preservation of the pylorus and PF appears in 3%-30% of patients [1,41,50,51] . It must be suspected when the amylase content of drained fluid is more than 3 times the normal value in the third postoperative day.…”
Section: Definition Of Pancreatic Fistulamentioning
confidence: 99%
“…Basically, three types of PG have been described: (1) in classic duct-to-mucosa anastomosis the pancreatic stump is sutured to the seromuscular layer of the gastric wall, while the MPD is sutured to the full-thickness stomach [32] , with or without a lost pancreatic stent; (2) in pancreatic stump intussusception into the stomach, the distance between the surface of the stump and the suture is longer, thus decreasing the risk of a fistula between the stitches that cross the pancreatic capsule. Suturing can be performed from the posterior gastric surface or from the inside of the gastric cavity through an anterior gastrostomy [33] .…”
Section: Types Of Pancreatogastrostomiesmentioning
confidence: 99%
See 1 more Smart Citation